1998
DOI: 10.1093/nar/26.23.5486
|View full text |Cite
|
Sign up to set email alerts
|

At least three linear regions but not the zinc-finger domain of U1C protein are exposed at the surface of the protein in solution and on the human spliceosomal U1 snRNP particle

Abstract: No structural information on U1C protein either in its free state or bound to the spliceosomal U1 small nuclear ribonucleoprotein (snRNP) particle is currently available. Using rabbit antibodies raised against a complete set of 15 U1C overlapping synthetic peptides (16-30 residues long) in different immunochemical tests, linear regions exposed at the surface of free and U1 snRNP-bound U1C were identified. Epitopes within at least three regions spanning residues 31-62, 85-103 and 116-159 were recognized on free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Anti‐U1A antibodies (856; Kambach and Mattaj, 1992), anti‐TIA‐1 (anti‐2G9; Anderson et al ., 1990), anti‐U170k (16H3; Neugebauer et al ., 1995) and anti‐U1C (Dumortier et al ., 1998) were bound to protein A–Sepharose beads and incubated in 15 μl of nuclear extracts complemented with buffer D to a total volume of 25 μl for 30 min on ice. After addition of 60 μl of IPP 150 buffer (10 mM Tris pH 8.0, 150 mM NaCl, 0.1% NP‐40), the reaction was incubated for 2 h on a rotating wheel at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti‐U1A antibodies (856; Kambach and Mattaj, 1992), anti‐TIA‐1 (anti‐2G9; Anderson et al ., 1990), anti‐U170k (16H3; Neugebauer et al ., 1995) and anti‐U1C (Dumortier et al ., 1998) were bound to protein A–Sepharose beads and incubated in 15 μl of nuclear extracts complemented with buffer D to a total volume of 25 μl for 30 min on ice. After addition of 60 μl of IPP 150 buffer (10 mM Tris pH 8.0, 150 mM NaCl, 0.1% NP‐40), the reaction was incubated for 2 h on a rotating wheel at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…for 1 min, the pellet was resuspended in SDS loading buffer, fractionated together with the aliquot of supernatant by electrophoresis on a 10–15% SDS–polyacrylamide gel and transferred onto nitrocellulose (Schleicher & Schuell). The blots were probed with anti‐TIA‐1, anti‐U1A, anti‐U1A/U2B″, anti‐U1‐70k, anti‐U1C (Dumortier et al ., 1998; Hoet et al ., 1998), anti‐Sm (Y12; Pisetsky and Lerner, 1982) or anti‐GST antibodies. HRP‐conjugated anti‐mouse or anti‐rabbit antibodies were used as secondary reagents, and visualized by enhanced chemoluminescence (ECL; Amersham).…”
Section: Methodsmentioning
confidence: 99%
“…They are used primarily because they can detect the surface exposed motifs. Typically this involves raising an antibody to a peptide that expresses the motif and then using this antibody to test the surface exposure or accessibility of the motif (for an example of this technique see (123)). The precise structure, or lack thereof, of bound peptides and motifs to domains or antibodies is not known in the majority of cases.…”
Section: Antibodies As Tools For the Experimental Investigation Of Mo...mentioning
confidence: 99%
“…The U1-C protein contains a C 2 H 2 -type zinc finger motif and does not bind to the snRNA but contacts U1-70k and B/B'. The interaction to U1-70k is mediated by the N-terminal zinc finger, which is not accessible to antibodies when U1-C is bound to U1 snRNP (Dumortier et al, 1998). Furthermore, U1-C has been implicated in 5' splice site binding by UV crosslinking assays (Nelissen et al, 1994(Nelissen et al, , 1991aRossi et al, 1996;Du and Rosbash, 2002).…”
Section: U1 Snrnpmentioning
confidence: 99%
“…The U1-C zinc finger comprises around 30-40 residues and is too small to be visualized on the SDS gel. However it has been shown that the N-terminus of U1-C, comprising the Zn-finger, is buried in the U1 snRNP particle (Dumortier et al, 1998). Depending on whether the U1-70k binding site was truncated or not, an N-terminal fragment of U1-C was presumably part of a degraded U1 snRNP.…”
Section: Limited Proteolysis Of U1 Snrnpmentioning
confidence: 99%